The association between pro- and anti-inflammatory cytokine polymorphisms and periventricular leukomalacia in newborns with hypoxic-ischemic encephalopathy - Gabriel ML (Dove Medical Press, 2016)
Marta Lúcia Gabriel,1 Fernanda Braojos Braga,1 Mariana Rodero Cardoso,1 Ana Cláudia Lopes,2 Vânia Belintani Piatto,2 Antônio Soares Souza1 1Radiology Department, 2Morphology Department, São José do Rio Preto Medical School, FAMERP, São Paulo, BrazilBackground: Periventricular leukomalacia (PVL) is a frequent consequence of hypoxic-ischemic injury. Functional cytokine gene variants that result in altered production of inflammatory (tumor necrosis factor-alpha [TNF-α] and interleukin-1beta [IL-1β]) or anti-inflammatory (interleukin-10 [IL-10]) cytokines may modify disease processes, including PVL.Objective: The aim of this study was to evaluate if there is a relationship between the two proinflammatory polymorphisms (TNF-σ-1031T/C and IL-1 β-511C/T) and the anti-inflammatory polymorphism IL-10-1082G/A and PVL risk in Brazilian newborns with and without this injury.Materials and methods: A cross-sectional case-control study performed at the Neonatal Intensive Care Unit of the Children's Hospital and Maternity of the São José do Rio Preto Medical School (FAMERP). Fifty preterm and term newborns were examined as index cases and 50 term newborns as controls, of both sexes for both groups. DNA was extracted from peripheral blood leukocytes, and the sites that encompassed the three polymorphisms were amplified by polymerase chain reaction-restriction fragment length polymorphism.Results: Gestational age ranged from 25 to 39 weeks, in the case group, and in the control group it ranged from 38 to 42.5 weeks (P<0.0001). Statistically significant association was found between TNF-α-1031T/C high expression genotype TC (odds ratio [OR], 2.495; 95% confidence interval [CI], 1.10–5.63; P=0.043) as well as between genotypes (TC + CC) (OR, 2.471; 95% CI, 1.10–5.55; P=0.044) and risk of PVL. Statistically significant association was found between IL-1β-511C/T high expression genotypes (CT + TT) (OR, 23.120; 95% CI, 1.31–409.4; P=0.003) and risk of PVL. Statistically significant association between IL-10-1082G/A high expression genotype GG (OR, 0.07407; 95% CI, 0.02–0.34; P<0.0001) as well as between IL-10-1082G high expression allele (OR, 0.5098; 95% CI, 0.29–0.91; P=0,030) and PVL reduced risk was observed. There was a statistically significant association between TC/CT/GA genotype combination and the risk of PVL (OR, 6.469; 95% CI, 2.00–20.92; P=0.001).Conclusion: There is evidence of an association between the polymorphisms TNF-α-1031T/C, IL-1β-511C/T, and IL-10-1082G/A and PVL risk in this Brazilian newborn population studied.Keywords: leukomalacia periventricular, tumor necrosis factor-alpha, interleukin-10, interleukin-1beta, polymorphism single nucleotide